Relation of Vitamin D Status to Congestive Heart Failure and Cardiovascular Events in Dogs. (7th November 2013) - Kraus, M.S.; Rassnick, K.M.; Wakshlag, J.J.; Gelzer, A.R.M.; Waxman, A.S.; Struble, A.M.; Refsal, K.
<x xml:space="preserve">Abstract</x> Background Vitamin D plays a pivotal role in cardiac function, and there is increasing evidence that vitamin D deficiency is associated with the development of congestive heart failure (CHF) in people. Hypothesis Serum vitamin D concentration is lower in dogs with CHF compared with unaffected controls and serum vitamin D concentration is associated with clinical outcome in dogs with CHF. Animals Eighty‐two client‐owned dogs. Methods In this cross‐sectional study, we examined the association between circulating 25‐hydroxyvitamin D [25(OH)D], a measure of vitamin D status, and CHF in dogs. In the prospective cohort study, we examined whether 25(OH)D serum concentration was associated with clinical outcome in dogs with CHF. Results Mean 25(OH)D concentration (100 ± 44 nmol/L) in 31 dogs with CHF was significantly lower than that of 51 unaffected dogs (123 ± 42 nmol/L; P = .023). The mean calculated vitamin D intake per kg of metabolic body weight in dogs with CHF was no different from that of unaffected dogs (1.37 ± 0.90 μg/kg metabolic body weight versus 0.98 ± 0.59 μg/kg body weight, respectively, P = .097). There was a significant association of serum 25(OH)D concentration on time to clinical manifestation of CHF or sudden death (P = .02). Conclusion and Clinical Relevance These findings suggest that low concentrations of 25(OH)D may be a risk factor for CHF in dogs. Low serum 25(OH)D concentration was associated with poor outcome in dogs with CHF. Strategies to improve vitamin D status in some dogs with CHF may prove beneficial without causing toxicity.